OC-004 Lorec registry – interim analysis of operative technique, pathology and oncological outcomes after abdomino-perineal excision. (22nd June 2015) - Jones, H; Crane, S; Moran, B; Cunningham, C
Abstract : Introduction: The LOREC perineal wound healing registry was developed to record data on abdomino-perineal excision (APE) for rectal cancer in colorectal units across the UK between 2012 and 2014 to understand current practice. Initial interim results are reported. Method: Surgeons wishing to participate received secure web-based access to the registry. Collected data included pre-operative staging, neo-adjuvant treatment, operative details, pathology, early outcome and follow-up at 12 months. Results: Overall 43 units entered a total of 259 patients undergoing APE. These included 168 extralevator APE (ELAPE) procedures (65%) and 91 non-ELAPEs, comprising 73 'standard' APE, 9 intersphincteric, 2 ischioanal and 7 unspecified procedures. The ELAPE and non-ELAPE groups are compared. This indication for APE was oncological in 98% with only 5 cases having APE for functional reasons, eg weak sphincters. On pre-op MRI the ELAPE group had higher grade tumours, with 112 (67%) staged on MRI as T3/4 compared with 47 (54%) for non-ELAPEs. ELAPEs also had a higher incidence of predicted positive lymph nodes, with 97 (58%) N1/2 compared with 38 (43%) for non-ELAPEs. The circumferential resection margin was predicted as less likely to be clear in the ELAPE group, 68 (45%), versus 38 (53%) in the non-ELAPE group. Metastatic disease was reported in 6% of the ELAPE group and 3% of the non-ELAPEs. The majority of patients received pre-operative treatment, most commonly chemoradiotherapy. Overall, the response to treatment was graded on MRI as mixed fibrosis and tumour in 32%, while 38% showed mainly or only tumour and 29% showed small or no residual tumour. Multivisceral resection was undertaken in 19 (11%) of ELAPEs and 7 (8%) of non-ELAPEs, the vast majority involving the vagina. Operative complications were recorded in 8%. These included rectal perforation (7 cases), urethral injury (6 cases), ureteric injury (2 cases) and 9 cases of 'other' complications. On pathology similar proportions had higher grade tumours: 81 (52%) T3/4 in the ELAPE group compared with the 41 (47%) in the non-ELAPE group. The ELAPEs were more likely to be node-positive, 55 (35%), versus 23 (27%) in the non-ELAPEs. A positive resection margin was reported in 21 (14%) of ELAPEs and 2 (2%) of non-ELAPEs. Perforation was noted in 3 patients in each group. The quality of TME was graded as mesorectal plane intact in 112 (67%) of ELAPEs and 46 (51%) of non-ELAPEs. The quality of the levator plane was graded as complete levator wrap in 110 (65%) of ELAPEs. Conclusion: It appears that surgeons are using ELAPE in more advanced cases but R1 rates of 14% suggest these are challenging and further means of improving outcomes should be explored. Disclosure of interest: None Declared.